AI SOLUTIONS IN BUILDING NATIONAL CYBER MONITORING AND CRISIS INCIDENT MANAGEMENT SYSTEMS - Рудницький, Олексій (SWorldJournal, 2025)
The article presents a systematic generalization and typology of artificial intelligence technologies applied not in the general context of cybersecurity but specifically for national cyber monitoring and crisis incident management. For the first time wit